Delving into Autophagy: Utilizing Natural Bioactive Compounds toCombat Alzheimer's Disease - Singh, Archna; Mazumder, Avijit; Das, Saumya; Kanda, Anmol; Mishra, Rashmi; Chaitanya, Motamarri Venkata Naga Lalitha (Current Bioactive Compounds, 2025)
Autophagy involves breaking down entire cell components, including organelles and macromolecules found in the cytoplasm of eukaryotic cells, especially proteins with extended lifespans. Pharmacological, therapeutic, and herbal methods are crucial throughout this deteriorating phase. Autophagy is a widespread and historically conserved process that occurs in all eukaryotic cells. The significance lies in cell malfunction impacting the autophagy process, which is associated with various significant conditions such as neurological and metabolic disorders in the brain. The role of various autophagic genes is also important in the positive regulation of autophagy. This research will provide a concise summary of various forms of autophagy, their molecular processes, their relationships to neuronal health, and the function of natural chemicals in the enhancement of autophagy. However, the focus of this work is on different ways to encourage autophagy. It is possible to treat metabolic neurodegenerative illnesses by triggering this process with a range of herbal and natural substances. In this article, these topics are explored and debated.
Keywords: Alzheimer’s disease